Military expenditure, foreign direct investments and economic growth a cross-country analysis of the ASEAN region - Cuevas, Isabel Lorraine A. (School of Economics, University of the Philippines Diliman, 2019)
Using a panel data of the ASEAN countries for the period 2008 to 2017, we analyzed the effect of military expenditure on economic growth. Two possible channels by which military expenditure affects growth are considered. First, a direct causal pathway shows that the impact of military spending on growth is stimulated by the government. Second, an indirect effect presents FDI as a causal pathway of military expenditure to growth. Four models were used to look into the relationships between the three variables. Results show that military expenditure does not have a direct effect on growth. However, it does have an indirect effect. As military spending increases, FDI inflow decreases. Moreover, FDI spurs growth. This shows that military expenditure has a negative effect on economic growth when FDI acts as a causal pathway.